The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pmed.1003474
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular health metrics from mid- to late-life and risk of dementia: A population-based cohort study in Finland

Abstract: Background Very few studies have explored the patterns of cardiovascular health (CVH) metrics in midlife and late life in relation to risk of dementia. We examined the associations of composite CVH metrics from midlife to late life with risk of incident dementia. Methods and findings This cohort study included 1,449 participants from the Finnish Cardiovascular Risk Factors, Aging, and Dementia (CAIDE) study, who were followed from midlife (baseline from1972 to 1987; mean age 50.4 years; 62.1% female) to late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 42 publications
8
59
0
1
Order By: Relevance
“…Better levels of smoking, BMI, glucose, and cholesterol were associated with worse cognitive function. Relatedly, a recent study found that the association of ideal LS7 with a reduced dementia risk was mainly present at mid-life, which was explained by age-varying association between biological health factors and risk of dementia [37]. Similar age-differential patterns have also been observed for other vascular risk scores, such as the Framingham general cardiovascular risk score [44].…”
Section: Ls7 Individual Metricsmentioning
confidence: 57%
See 1 more Smart Citation
“…Better levels of smoking, BMI, glucose, and cholesterol were associated with worse cognitive function. Relatedly, a recent study found that the association of ideal LS7 with a reduced dementia risk was mainly present at mid-life, which was explained by age-varying association between biological health factors and risk of dementia [37]. Similar age-differential patterns have also been observed for other vascular risk scores, such as the Framingham general cardiovascular risk score [44].…”
Section: Ls7 Individual Metricsmentioning
confidence: 57%
“…An additional aim of our study was to examine potentially different patterns for younger and older age groups. LS7 has so far mostly been applied to midlife populations, either exploring the link with dementia [16,32,37] or cognition [15,19,38]. However, Samieri et al [39] examined the associations of LS7 with cognitive decline and incident dementia in an older sample (mean age = 73.7 years).…”
Section: Total Ls7 Scorementioning
confidence: 99%
“…This is unfortunate as dementia risk reduction may offer greatest public health benefit in LMICs [98], which will bear greater future dementia burden [99] and likely have less access to advances in disease modifying treatments [100,101]. Similarly, beliefs in younger years can strongly influence behaviour patterns in the critical middle-age period [3,4,102]. Further primary research addressing these gaps will support stronger future reviews and model development.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…It has been suggested that cardiometabolic risk factors (eg, high blood pressure and high cholesterol), especially when occurring in midlife (eg, 40s–50s years of age), but not necessary in late‐life, could contribute to an increased risk of late‐life cognitive decline and dementia. 10 , 11 , 43 In this context, MIND‐China, as an intervention study in older adults (≥60 years of age), is not able to test the potential effect of control of midlife vascular risk factors on late‐life cognitive outcomes. In addition, we do not have AD biomarkers from CNS (eg, CSF and brain positron emission tomography‐computed tomography [PET/CT] scans) to validate plasma AD biomarkers in our study, although current evidence from literature shows clear correlations of SIMOA‐based plasma AD biomarkers with CNS AD biomarkers and we do have the plan to test additional blood biomarkers that are more sensitive for AD (eg, phosphorated‐tau 181, 217, and 231) in the future by using frozen baseline blood samples.…”
Section: Discussionmentioning
confidence: 99%